Efficient Generation and Arbitrary Manipulation of Chiral Terahertz Waves Emitted from Bi2Te3–Fe Heterostructures - Xinhou Chen; Hangtian Wang; Chun Wang; Chen Ouyang; Gaoshuai Wei; Tianxiao Nie; Weisheng Zhao; Jungang Miao; Yutong Li; Li Wang; Xiaojun Wu (Advanced Photonics Research, 2021)
Polarization arbitrary manipulated terahertz (THz) pulses with a prescribed amplitude temporal evolution and deposited electric‐field vectors can promote many disruptive technologies and enable enormous applications in polarization‐sensitive THz spectroscopy and imaging, ultrafast THz optospintronics, information encryption, and space exploration. However, the severe shortage of dynamically tunable THz polarization devices has impeded the proliferation of THz science and technology. Herein, a method of efficient generation and arbitrary manipulation of chiral THz waves in the topological insulator (TI)–iron (Fe) heterostructures through delicately engineering the linear photogalvanic effect (LPGE) and spin‐to‐charge conversion (SCC) effect induced by femtosecond laser pulses is proposed and demonstrated. Utilizing the intrinsic merits of optical‐controlled LPGE and magnetic field direction‐adjusted SCC effect, the TI–Fe can radiate chiral THz waves with arbitrarily tailored chirality and ellipticity. To verify the capability of such a novel chiral THz source, helical substructure associates THz circular dichroism spectroscopy is implemented on several (bio)materials, exemplified by the beetle exoskeletons. Furthermore, ultrafast switching between two THz chirality states can be realized by a double‐pulse excitation scheme. Such versatile chiral THz emitters with high efficiency and easy integration may have some disruptive applications.